Campylobacter colonization of broiler chickens - O'Kane, Peter Michael (2017)
Campylobacteriosis is a major cause of bacterial gastroenteritis in man. The primary causative organisms, Campylobacter jejuni and C. coli, colonize the chicken’s gastrointestinal tract and contaminated poultry meat is the primary mode of transmission to humans. This thesis examined factors influencing Campylobacter colonization of the chicken’s gastrointestinal tract and several potential interventions to reduce this. A novel in vivo ligated caecal loop model was developed using terminally anaesthetised broiler chickens. Previously unreported durations of stable anaesthesia, of up to 625 minutes, were achieved. This model was used to study real-time colonization of campylobacters in situ. Different responses of two robustly colonizing Campylobacter strains were noted; C. jejuni HPC5 counts invariably declined, whereas C. coli OR12 was capable of immediate growth within the caeca. The same model was used to test bacteriophage therapy of caeca pre-colonized with C. jejuni HPC5. No replication was observed for phage CP30 during the 6 hours studied. Replication was observed for phage CP20, but no decline of C. jejuni had occurred during the same timeframe. The genome of C. coli OR12 was sequenced to identify factors which contribute to its fitness in colonizing chickens. A large 2,033,093 base pair chromosome was assembled, in addition to three plasmids. The chromosome encodes a complete type VI secretion system and plasmid genes encode type IV secretion proteins. These may contribute to the ability of C. coli OR12 to out-compete other Campylobacter strains, and to resist environmental stresses. Campylobacter coli OR12 grows on aerobically incubated blood agar. Serial aerobic passage increased aerotolerance and peroxide stress resistance but motility, growth rate and cellular morphology were unaffected. Aerotolerance was associated with mutations to genes involved in central and carbohydrate metabolism. Aerotolerance may enhance extra-intestinal survival and transmission between host animals. A colonization model was used to test the effect of a live yeast as a putative competitive exclusion intervention against C. jejuni colonization of broiler chickens. No significant differences in caecal or faecal C. jejuni counts were noted, nor was growth rate or feed conversion efficiency affected by yeast supplementation. Analysis of the Campylobacter phage CP8 genome identified significant sequence identity of protein gp010 with the avian leukocyte receptor CD30 ligand. A plausible pathway exists for gp010 to influence the chicken’s immune response to Campylobacter, which would constitute trans-kingdom signalling. A tissue culture based reporter assay for activation of human CD30 receptor was developed. No significant agonistic or antagonistic activity of gp010 was demonstrated. Further in vitro and in vivo investigation is warranted. Collectively these findings further our knowledge of factors which may influence Campylobacter colonization of chickens and provide novel avenues for investigation.